In vivo and in vitro expression of steroid-converting enzymes in human breast tumours: associations with interleukin-6 - Speirs, V (Nature Publishing Group, 1999)
Enzymes modulating local steroid availability play an important role in the progression of human breast cancer. These include isoforms of 17β-hydroxysteroid dehydrogenase (17-HSD), aromatase and steroid sulphatase (STS). The aim of this study was to investigate the expression, by reverse transcription polymerase chain reaction, of 17-HSD types I–IV, aromatase and steroid STS in a series of 51 human breast tumour biopsies and 22 primary cultures of epithelial and stromal cells derived from these tumours, giving a profile of the steroid-regulating network for individual tumours. Correlations between enzyme expression profiles and expression of the interleukin (IL)-6 gene were also sought. All except one tumour expressed at least one isoform of 17-HSD, either alone or in combination with aromatase and STS. Expression of 17-HSD isoforms I–IV were observed in nine tumours. Of the 15 tumours which expressed three isoforms, a combination of 17-HSD II, III and IV was most common (6/15 samples). The majority of tumours (n = 17) expressed two isoforms of 17-HSD with combinations of 17-HSD II and IV predominant (7/17 samples). Eight tumours expressed a single isoform and of these, 17-HSD I was in the majority (5/8 samples). In primary epithelial cultures, enzyme expression was ranked: HSD I (86%) > STS (77%) > HSD II (59%) > HSD IV (50%) = aromatase (50%) > HSD III (32%). Incidence of enzyme expression was generally reduced in stromal cultures which were ranked: HSD I (68%) > STS (67%) > aromatase (48%) > HSD II (43%) > HSD IV (28%) > HSD III (19%). Expression of IL-6 was associated with tumours that expressed ≥ 3 steroid-converting enzymes. These tumours were of higher grade and tended to come from patients with family history of breast cancer. In conclusion, we propose that these enzymes work in tandem with cytokines thereby providing sufficient quantities of bioactive oestrogen from less active precursors which stimulates tumour growth. © 1999 Cancer Research Campaign